HUBUNGAN FAKTOR RISIKO IBU HAMIL DAN PAPARAN ASAP ROKOK DENGAN BERAT BAYI LAHIR RENDAH - Catur Wulandari (Jurnal Delima Harapan, 2017)
This study aimed to analyze the relationship between maternal factors (such us: age,birth spacing, chronic energy deficiency, anemia), and exposure to cigarette smoke withlow birth weigth infant. The study was a correlation study with retrospective approach.The subjects were 80 mothers who delivered both normal birth weight infants and lowbirth weight infants with a term gestational age in Hospital Dr. Harjono Ponorogo, thisresearch applied purposive sampling method. Data collection techniques were done byusing medical records and interview guidelines. Data were analyzed by logistic analysisof linear and processed with SPSS 18.0 for windows. There were 22.5% of pregnantwomen with high-risk age (<20 and >35 years), 8.8% of pregnant women with birthspacing <2 years, 18.8% of pregnant women with the status of chronic energy deficiency(LiLA <23.5 cm), 47.5% of pregnant women having mild anemia, 87.5% of pregnantwomen exposed to smoke. There is no correlation between age of pregnant women andlow birth weight (p = 0.155), but there was a correlation between birth spacing and lowbirth weight (p = 0.034), there was also a correlation between the status of chronicenergy deficiency of pregnant women and low birth weight (p = 0.039). Moreover, therewas a correlation between anemia in pregnant women and low birth weight (p = 0.047),and there was a correlation between exposure to cigarette smoke and low birth weigth (p= 0.001).